Los hogares latinoamericanos durante la segunda mitad del siglo XX : una perspectiva sociodemográfica - García, Brígida; Rojas, Olga Lorena (El Colegio de México A.C., 2002)
The aim of this paper is to analyze the most significant socio-demo- graphic changes that took place in Latin American households during the second half of the 20th century. It considers two key aspects: the possible convergence towards small, nuclear families and the nature and increase in the number of households with female headship. The paper not only seeks to summarize existing knowledge of these issues but also to focus on the links between socio-demographic changes in households and the persistent social and gender inequality in Latin America. Some of the main conclusions are: a) despite a definite trend towards the nuclearization of Latin American households, the importance of extended family arrangements continues to be a characteristic of the family system in the region, particularly among the low-income population, and b) there has been an evident increase in the number of women-headed household that may be occurring in several sectors of Latin American societies.